Penerapan Metode IPA dan PGCV untuk Menganalisis Kualitas Layanan PT. Bank X berdasarkan Dimensi Servqual - Howin, Rikko; Prasetya, Wibawa (Metris: Jurnal Sains dan Teknologi, 2020)
The bank is an institution that usually keeps people's money and redistributes it, as well as providing other services. The quality of service at the bank is important in order to compete well in the banking industry. This study aims to determine customer satisfaction, priority improvements needed to increase customer satisfaction. The data processing of this research begins with the validity and reliability test of the questionnaire, then continues with data processing using the SERVQUAL, IPA, and PGCV methods. In the SERVQUAL method there are a total of 22 attributes, for the tangible dimension it has 9 attributes, then the reliability dimension has 2 attributes, Furthermore, the responsiveness dimension has 4 attributes, the assurance dimension has 3 attributes, and finally the empathy dimension has 4 attributes. The result of Service Quality data processing, as a whole has a gap minus value. The results are then processed by the IPA method and the results show that six attributes are in the first quadrant (priority recovery), three attributes are in the second quadrant, one attribute is in the third quadrant, twelve attributes are in the fourth quadrant. The results of data processing using the IPA method, then continued with data processing using the PGCV method, and the results show that there are six attributes listed in the order of priority, with the highest PGCV score statement, namely the item "tellers and customers". Service has a sufficient number. Then followed by adding some divider walls, equity in bank services, in customer services speed, improvement at queue information, adding some chairs. So, to increase and maintain the bank service quality, the problems must be fixed immediately based on the priority rank results like adding some divider wall, increase the number of teller and customer service, adding some chair, improving equity in bank services, improving the customer service speed in serving customers